2019
DOI: 10.1111/ajo.12981
|View full text |Cite
|
Sign up to set email alerts
|

Survey on use of antenatal magnesium sulphate for fetal neuroprotection prior to preterm birth in Australia and New Zealand – Ongoing barriers and enablers

Abstract: Background Clinical practice guidelines recommend the use of antenatal magnesium sulphate for fetal neuroprotection before preterm birth at <30 weeks’ gestation. Aims This survey assessed the use of antenatal magnesium sulphate for fetal neuroprotection to determine if use has changed since the previous survey in 2012, and to evaluate enablers and barriers to use. Materials and Methods A questionnaire was sent to clinical leaders at 29 hospitals with a neonatal intensive care unit in Australia and New Zealand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 23 publications
(55 reference statements)
0
19
0
Order By: Relevance
“…Approximately 20 years after it was first suggested that magnesium sulphate might reduce cerebral palsy in children born preterm, and after more than 6000 fetuses were recruited into randomised controlled trials (RCTs), 6 antenatal magnesium sulphate for fetal neuroprotection was introduced in 2010 in Australia for women likely to deliver <30 weeks' gestational age 7 . Surveys subsequently reported that magnesium sulphate neuroprotection in high‐risk women had risen from 80% 8 in the early 2010s to 89% 9 in the late 2010s in Australia and New Zealand. Although surveys provide some insight, they do not measure precisely the translation of antenatal magnesium sulphate into clinical practice and its effects on rates of cerebral palsy in high‐risk infants, which need to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 20 years after it was first suggested that magnesium sulphate might reduce cerebral palsy in children born preterm, and after more than 6000 fetuses were recruited into randomised controlled trials (RCTs), 6 antenatal magnesium sulphate for fetal neuroprotection was introduced in 2010 in Australia for women likely to deliver <30 weeks' gestational age 7 . Surveys subsequently reported that magnesium sulphate neuroprotection in high‐risk women had risen from 80% 8 in the early 2010s to 89% 9 in the late 2010s in Australia and New Zealand. Although surveys provide some insight, they do not measure precisely the translation of antenatal magnesium sulphate into clinical practice and its effects on rates of cerebral palsy in high‐risk infants, which need to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a survey of perinatal clinicians throughout Australia and New Zealand in 2015, clinicians estimated that 89% of eligible mothers received magnesium sulphate. 18 Based on ANZNN data, the reality was closer to 60-70%. 6 Our study suggests that without Furthermore, our approach and model can be extrapolated to a larger data set such as the ANZNN.…”
Section: Discussionmentioning
confidence: 96%
“…These leaders could identify hospitalspecific enablers and barriers to implementation; location-specific solutions to these barriers; in-servicing solutions to support education for new staff; mechanisms to ensure educational materials are readily available, and could complete auditing of whether pregnant women are given CMV prevention advice to measure implementation progress. 26,31 New research is required to investigate whether these kinds of strategies would be useful for CMV prevention messaging, and whether they lead to a reduction in cCMV infection. This is the first CMV education course for midwives to be developed and evaluated in the Australian context.…”
Section: Discussionmentioning
confidence: 99%
“…A further limitation was that we did not explore what other strategies could support implementation of the CMV prevention guidelines beyond this education piece, for example engaging dedicated implementation leaders. These leaders could identify hospital‐specific enablers and barriers to implementation; location‐specific solutions to these barriers; in‐servicing solutions to support education for new staff; mechanisms to ensure educational materials are readily available, and could complete auditing of whether pregnant women are given CMV prevention advice to measure implementation progress 26,31 . New research is required to investigate whether these kinds of strategies would be useful for CMV prevention messaging, and whether they lead to a reduction in cCMV infection.…”
Section: Discussionmentioning
confidence: 99%